Pengaruh Keandalan, Ketanggapan, Kepastian, Perhatian dan Tangibilitas Layanan terhadap Kepuasan Mahasiswa STAIN - Sunardji Dahri Tiam (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
The purposes of the correlation research are to search the influence of reliability, responsiveness, assurance, empathy, and tangibility on the students' satisfaction. The field of this research was in STAIN Pamekasan. Subjects of the research were 233 through stratified random sampling. The research instruments were questionnaire. The collected data were analyzed by regression analysis. The research found that there were significant correlation reliability, responsiveness, assurance, empathy, tangibility, and the students' satisfaction.